Immunosequencing of the T-cell receptor repertoire reveals signatures specific for diagnosis and characterization of early Lyme disease - Greissl, Julia; Pesesky, Mitch; C. Dalai, Sudeb; W. Rebman, Alison; J. Soloski, Mark; J. Horn, Elizabeth; N. Dines, Jennifer; M. Gittelman, Rachel; M. Snyder, Thomas; O. Emerson, Ryan; Meeds, Ted; Manley, Thomas; et al. (medRxiv, 2021)
Lyme disease, the most common tick-borne illness in the United States, is most frequently caused by infection with Borrelia burgdorferi. Although early antibiotic treatment can prevent development of severe illness and late manifestations, diagnosis is challenging in patients who do not present with a typical erythema migrans rash. To support a diagnosis of Lyme disease in such cases, guidelines recommend 2-tiered serologic testing. However, 2-tiered testing has numerous limitations, including ambiguity in interpretation and lower sensitivity in early disease. We developed a diagnostic approach for Lyme disease based on the T-cell response to B. burgdorferi infection by immunosequencing T-cell receptor (TCR) repertoires in blood samples from 3 independent cohorts of patients with laboratory-confirmed or clinically diagnosed early Lyme disease, as well as endemic and non-endemic controls. We identified 251 public, Lyme-associated TCRs that were used to train a classifier for detection of early Lyme disease with 99% specificity. In a validation cohort of individuals with early Lyme disease, TCR testing demonstrated a 1.9-fold increase in sensitivity compared to standard 2-tiered testing (STTT; 56% versus 30%), with a 3.1-fold increase ≤4 days from the onset of symptoms (44% versus 14%). TCR positivity predicted subsequent seroconversion in 37% of initially STTT-negative patients, suggesting that the T-cell response is detectable before the humoral response. While positivity for both tests declined after treatment, greater declines in posttreatment sensitivity were observed for STTT compared to TCR testing. Higher TCR scores were associated with clinical measures of disease severity, including abnormal liver function test results, disseminated rash, and number of symptoms. A subset of Lyme-associated TCRs mapped to B. burgdorferi antigens, demonstrating high specificity of a TCR immunosequencing approach. These results support the clinical utility of T-cell‒based testing as a sensitive and specific diagnostic for early Lyme disease, particularly in the initial days of illness.